Evaluation of Reducing the Excess Abdominal Skin, Subcutaneous Tissue and Anterior Abdominal Wall Laxity: A Prospective Observational Study at Dhaka Medical College Hospital - Ahmed, Dr. Iqbal; Hossain, Dr. Md Farouqe; Asaduzzaman, Dr. Md.; Chowdhury, Dr. Riffat (International Journal of Medical Science and Clinical Research Studies, 2023)
Background: Lax abdominal muscles cause laxity or bulging. This is generally a consequence of age or post-pregnancy, causing the abdominal rectus muscles and fascia that overlies and divides them to weaken. Abdominoplasty, a popular cosmetic surgery, has improved in recent years. helped minimize abdominal fat and skin. Medical institutions are diagnosing and treating obesity at an increasing pace. Objective: The purpose of the study was reduce the excess abdominal skin,subcutaneous tissue and anterior abdominal wall laxity. Methods: The duration of this prospective observational research was from July 2014 to April 2015. The research population consisted of patients hospitalized to the Plastic Surgery Department of Dhaka Medical College Hospital and numerous private hospitals in Dhaka with extra abdominal skin and abdominal wall laxity owing to various causes, such as past pregnancy or severe weight loss. From the study population, 30 instances that satisfied the enrollment requirements were chosen. Results: The majority of patients (26, or 86.67 %) were female, and 76 % were married. At the time of surgery, the average age was 41.3 years. The total complication rate was 40%, with just four serious complications (13.33%) and the most being mild (9, 30 % ). Seroma (3, 10%), infection (2, 6.67%), hematoma (2, 6.67%), wound dehiscence (1, 3.33%), partial flap loss (2, 6.67%), umbilical stenosis (1, 3.33%), epidermolysis (1, 3.33%), DVT (1, 3.33%) were the most prevalent complications (1, 3.33 % ). Very excellent (19, 66.3%), good (9, 30%), and adequate were patients’ ratings of satisfaction (2, 6 % ). No patient reported low or extremely bad satisfaction. Conclusion: Abdominoplasty may be done with little risk and provides excellent results. Patients reported relief from their symptoms and satisfaction with the result. However, there was a high rate of mild problems, most of which involved wound healing. At most cases, problems were mild and quickly treated in a doctor’s office.